2017
DOI: 10.1007/s10530-017-1428-y
|View full text |Cite
|
Sign up to set email alerts
|

Present and future distribution of three aquatic plants taxa across the world: decrease in native and increase in invasive ranges

Abstract: International audienceInland aquatic ecosystems are vulnerable to both climate change and biological invasion at broad spatial scales. The aim of this study was to establish the current and future potential distribution of three invasive plant taxa, Egeria densa, Myriophyllum aquaticum and Ludwigia spp., in their native and exotic ranges. We used species distribution models (SDMs), with nine different algorithms and three global circulation models, and we restricted the suitability maps to cells containing aqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 59 publications
6
73
1
2
Order By: Relevance
“…Several studies have found that terrestrial macroclimatic variables are useful when developing SDMs for aquatic species (Gallardo et al, ; Kelly et al, ; Reshetnikov & Ficetola, ; Rodríguez‐Merino, García‐Murillo, Cirujano, & Fernández‐Zamudio, ). In this study, the climatic variables with the greatest predictive value were annual mean temperature and precipitation in the driest quarter, which concurs with the findings of other similar studies (Gillard, Thiébaut, Deleu, & Leroy, ; Rodríguez‐Merino et al, ). These results support the hypothesis that climate drives large‐scale species distribution patterns (Pearson & Dawson, ).…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have found that terrestrial macroclimatic variables are useful when developing SDMs for aquatic species (Gallardo et al, ; Kelly et al, ; Reshetnikov & Ficetola, ; Rodríguez‐Merino, García‐Murillo, Cirujano, & Fernández‐Zamudio, ). In this study, the climatic variables with the greatest predictive value were annual mean temperature and precipitation in the driest quarter, which concurs with the findings of other similar studies (Gillard, Thiébaut, Deleu, & Leroy, ; Rodríguez‐Merino et al, ). These results support the hypothesis that climate drives large‐scale species distribution patterns (Pearson & Dawson, ).…”
Section: Discussionsupporting
confidence: 93%
“…Rise in temperature supports in dispersion of the invasive species to the greater range (71). In high gas emission scenario, invasive species tends to occupy or increase their habitat range by two-fold by 2070 (71). Our model has exhibited annual mean temperature and annual range temperature as important bioclimatic variables.…”
Section: Discussionmentioning
confidence: 84%
“…Study suggests that Mikania micrantha is spreading in aggressive way and has created problem in component of biodiversity like in forest cover, water availability, agriculture and even in grassland (66,69,70). Rise in temperature supports in dispersion of the invasive species to the greater range (71). In high gas emission scenario, invasive species tends to occupy or increase their habitat range by two-fold by 2070 (71).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, it is most likely that future hotspots of invasions might be located in newly industrialized and developing economies (see Dyer et al, 2017 for birds). Another potential bias comes from the lack of distinction between native and alien ranges where climate change effects can be divergent, as recently suggested for three invasive freshwater macrophytes that were predicted to increase in their alien range but decrease in their native range (Gillard, Thiebaut, Deleu, & Leroy, 2017). Although the most damaging impacts from some IAS occur on islands (Bellard, Rysman, Leroy, Claud, & Mace, 2017) and eradication programs are mainly implemented there (Jones et al, 2016), most of the studies analyzed here focused on mainland systems (except for Hawaii and New Zealand).…”
Section: Current Biasesmentioning
confidence: 99%